The effectiveness of Instagram influencer towards consumers purchase intention / Norasnida Sahak - Sahak, Norasnida (Faculty of Business and Management, 2019)
This study is aimed to identify the effectiveness of Instagram influencers towards consumers purchase intention. The factors involved in this study were credibility and attractiveness. Convenient sampling technique was adapted and questionnaires were distributed to respondents among students in Universiti Teknologi MARA Cawangan Melaka Kampus Bandaraya Melaka through online questionnaires using Google Form platform. A total of 171 questionnaires were answered and were found usable. Collected data were analysed using Statistical Package for Social Science (SPSS) version 22. Hence, the data were analysed using several statistical analysis including frequencies distribution analysis, descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis. The result revealed that credibility of the influencer has the highest relationship value towards consumers purchase intention. Furthermore, the study findings confirmed that both variables are positively related to the consumers purchase intention. As a conclusion, the findings of this study can be beneficial for future researchers, practitioners and government agencies.